2022
DOI: 10.3390/polym14245477
|View full text |Cite
|
Sign up to set email alerts
|

Anomalous Strain Recovery after Stress Removal of Graded Rubber

Abstract: Mechanical responses after the uniaxial deformation of graded styrene–butadiene rubber (SBR) with a gradient in the crosslink points in the thickness direction were investigated as compared with those of homogenously vulcanized SBR samples. The elongational residual strain of a graded sample was found to depend on the part with a high crosslink density. Therefore, it showed good rubber elasticity. After stress removal, moreover, the graded sample showed a marked warpage. This suggested that shrinking stress ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…Subsequently, the no/few crosslinks side shinks. This requires a change in the conformation of the chain segments, which takes a long time, as explained in detail in our preceding paper 17 . Considering this mechanism, the large residual strains were not the equilibrium ones, at least not at 0.017 s −1 .…”
Section: Resultsmentioning
confidence: 89%
See 4 more Smart Citations
“…Subsequently, the no/few crosslinks side shinks. This requires a change in the conformation of the chain segments, which takes a long time, as explained in detail in our preceding paper 17 . Considering this mechanism, the large residual strains were not the equilibrium ones, at least not at 0.017 s −1 .…”
Section: Resultsmentioning
confidence: 89%
“…This demonstrated that the hysteresis loops were affected by the duration of loading. We previously investigated a graded rubber that exhibited favorable rubber elasticity, that is, a small residual strain, although it took a very long time to recover after the removal of stress 17 . When stretched, chain orientation in the no/few crosslinks side is relaxed (see Figure S5).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations